2013
DOI: 10.1177/1721727x1301100209
|View full text |Cite
|
Sign up to set email alerts
|

High Avidity Anti-β2-Glycoprotein i Antibodies Activate Human Coronary Artery Endothelial Cells and Trigger Peripheral Blood Mononuclear Cell Migration

Abstract: Anti-p2-glycoprotein I antibodies (ap2GPI) represent a potential pathogenic candidate for coronary artery diseases. High avidity ap2GPI (HAv ap2GPI) are known to be associated with thrombotic and obstetric manifestations in patients with antiphospholipid syndrome, who are also susceptible to the development of premature atherosclerosis. However, there is little information about how human coronary artery endothelial cells (HCAEC) are affected by HAv ap2GPI. The purpose of our study was to evaluate the pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
(46 reference statements)
1
14
2
Order By: Relevance
“…Interestingly, positivity to peptide B more likely occurred in patients with only APS as compared to patients with APS associated with SLE, while the opposite association was detected for positivity of same sera for peptides C and F. On the other hand, the positivity for peptide A was a stronger predictor for the presence of LAv anti-b2GPI as compared to HAv IgG anti-b2GPI. The clinical study by Shoenfeld et al on 295 patients with APS showed that the positivity for peptide A ( 58 LKTPRV 63 ; domains I-II) was negatively associated with overall thrombosis [34]. The study also revealed that anti-peptide C antibodies were a significant predictor of recurrent spontaneous abortions [34], which was not confirmed in our study.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Interestingly, positivity to peptide B more likely occurred in patients with only APS as compared to patients with APS associated with SLE, while the opposite association was detected for positivity of same sera for peptides C and F. On the other hand, the positivity for peptide A was a stronger predictor for the presence of LAv anti-b2GPI as compared to HAv IgG anti-b2GPI. The clinical study by Shoenfeld et al on 295 patients with APS showed that the positivity for peptide A ( 58 LKTPRV 63 ; domains I-II) was negatively associated with overall thrombosis [34]. The study also revealed that anti-peptide C antibodies were a significant predictor of recurrent spontaneous abortions [34], which was not confirmed in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…The clinical study by Shoenfeld et al on 295 patients with APS showed that the positivity for peptide A ( 58 LKTPRV 63 ; domains I-II) was negatively associated with overall thrombosis [34]. The study also revealed that anti-peptide C antibodies were a significant predictor of recurrent spontaneous abortions [34], which was not confirmed in our study. However, peptide C was significantly involved in the prediction of overall thrombosis (negatively) and disease type (APS associated with SLE).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Oxidatively altered IgG (oxIgG) with increased immunoreactivity to β2GPI and its peptide clusters influence human coronary artery endothelial cells. 62 42 The amino acid sequence QGPAHSK represents a mimotope of the conformational epitope that resides on the third domain of β2GPI and is recognized by more than 30% share of high-avidity anti-β2GPI antibodies. The amino acid sequence KMDGNHP represents a mimotope of the conformational epitope between the third and fourth domain of β2GPI that is recognized by more than 30% share of polyclonal low avidity anti-β2GPI antibodies when β2GPI is in open conformation.…”
Section: Biological Materialsmentioning
confidence: 99%